Indoleamine 2,3-Dioxygenase 2 Immunohistochemical Expression in Resected Human Non-small Cell Lung Cancer: A Potential New Prognostic Tool - Mandarano, Martina; Bellezza, Guido; Belladonna, Maria Laura; Vannucci, Jacopo; Gili, Alessio; Ferri, Ivana; Lupi, Chiara; Ludovini, Vienna; Falabella, Giulia; Metro, Giulio; Mondanelli, Giada; Chiari, Rita; et al. (Frontiers in Immunology, 2020)
Indoleamine 2,3-dioxygenase 2 (IDO2) is an analog of the tryptophan degrading and immunomodulating enzyme indoleamine 2,3-dioxygenase 1 (IDO1). Although the role of IDO1 is largely understood, the function of IDO2 is not yet well elucidated. IDO2 overexpression was documented in some human tumors, but the linkage between IDO2 expression and cancer progression is still unclear, in particular in non-small cell lung cancer (NSCLC). Immunohistochemical expression and cellular localization of IDO2 was evaluated on 191 formalin-fixed and paraffin-embedded resected NSCLC. Correlations between IDO2 expression, clinical-pathological data, tumor-infiltrating lymphocytes (TILs), immunosuppressive tumor molecules (IDO1 and programmed cell death ligand-1 – PD-L1 –) and patients’ prognosis were evaluated. IDO2 high expression is strictly related to high PD-L1 level among squamous cell carcinomas group (p=0.012), to either intratumoral or mixed localization of TILs (p<0.001) and to adenocarcinoma histotype (p<0.001). Furthermore, a significant correlation between IDO2 high expression and poor non-small cell lung cancer prognosis was detected (p=0.011). The current study reaches interesting knowledge about IDO2 in non-small cell lung cancer. The close relationship between IDO2 expression, PD-L1 increased levels, TILs localization and NSCLC poor prognosis, assumed IDO2 as a potential prognostic biomarker to be exploited for optimizing innovative combined therapies with immune checkpoint inhibitors.